2009
DOI: 10.1007/s11325-009-0318-7
|View full text |Cite
|
Sign up to set email alerts
|

Soft palate length and upper airway relationship in OSA and non-OSA subjects

Abstract: Background-The narrowest area of the airway between the posterior nasal opening and the epiglottis is usually located in the retro palatal area. Many consider this the most likely site of airway obstruction during an obstructive sleep apnea (OSA) event. The aim of this study was to investigate the differences in soft palate and airway length between OSA and non-OSA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 13 publications
3
39
0
1
Order By: Relevance
“…Correlation analyses between log-AHI and clinic-biomarkers including cephalometric indices showed a positive correlation between log-AHI and soft pal- high prevalence of SDB in Japanese patients with acromegaly (87.5%), consistent with previous studies in Europeans [13][14][15][16], 2) the severity of SDB in these patients correlated with a large soft palate, as previous report showed that soft palate length was significantly larger in OSA patients compared to controls [30]. Previous report in Japanese acromegalic patients showed that all oximetric parameters with a bedside oximeter showed worsen results in SDB group than in non-SDB group [17], but the present study investigated the relationship between the severity of SDB (i.e.…”
Section: Correlation Analysis Between Ahi and Measured Parameterssupporting
confidence: 89%
See 1 more Smart Citation
“…Correlation analyses between log-AHI and clinic-biomarkers including cephalometric indices showed a positive correlation between log-AHI and soft pal- high prevalence of SDB in Japanese patients with acromegaly (87.5%), consistent with previous studies in Europeans [13][14][15][16], 2) the severity of SDB in these patients correlated with a large soft palate, as previous report showed that soft palate length was significantly larger in OSA patients compared to controls [30]. Previous report in Japanese acromegalic patients showed that all oximetric parameters with a bedside oximeter showed worsen results in SDB group than in non-SDB group [17], but the present study investigated the relationship between the severity of SDB (i.e.…”
Section: Correlation Analysis Between Ahi and Measured Parameterssupporting
confidence: 89%
“…AHI) with cardiorespiratory monitoring and various parameters in Japanese acromegalic patients, which to our knowledge is the first such report. Previous studies in European acromegalic patients showed that SDB correlates with high levels of GH and IGF-1 [3,13,15], aging [10,12,14,15], male gender, BMI [14], WC [14], neck circumference [15] and tongue size [30,31]. Although we reported previously that AHI correlated with BMI and WC in diabetic patients [20,21], the present study found no correlation between AHI and BMI and WC in acromegalic patients (Table 2), probably because acromegaly is often a disease with little fat but organ hypertrophy, different from diabetes.…”
Section: Correlation Analysis Between Ahi and Measured Parametersmentioning
confidence: 99%
“…In individuals with obstructive sleep apnea, the length of the soft palate may be increased, compared with the individuals that do not present this disturbance and they present reduction in the dimensions of the nasopharynx and oropharynx 18 . Therefore, one should be cautious about surgical movements, even in individuals who do not present signs and symptoms of apnea, in order to avoid elongation by displacement of this structure, and the reduction in oropharyngeal and nasopharyngeal space, thereby hindering the passage of air.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that the airway is anatomically smaller in snorers and OSAS patients. In many studies, the most affected area in patients with sleep apnea is the retropalatal region of the oropharynx [8][9][10] . It is stated in the study of Ahn et al one of the reasons of narrowness in retropalatal area was increase in volume of tongue 11 .…”
Section: Discussionmentioning
confidence: 99%